2020
DOI: 10.1080/00223131.2020.1720845
|View full text |Cite
|
Sign up to set email alerts
|

Remote detection of radioactive hotspot using a Compton camera mounted on a moving multi-copter drone above a contaminated area in Fukushima

Abstract: Torii (2020) Remote detection of radioactive hotspot using a Compton camera mounted on a moving multi-copter drone above a contaminated area in Fukushima,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Since the contamination can be anywhere in a building, a 4 Compton camera is being developed. Sato et al [ 187 ] also performed radiation imaging while the platform is moving by measuring the self-position and posture of the camera in each detection (using time stamps), which allowed extraction of the direction of the Compton cones. Replacing the gamma imager by a 3D-LiDAR, it was also possible to do a second autonomous flight to obtain the 3D topographical measurement and to create a 3D radiation distribution map.…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the contamination can be anywhere in a building, a 4 Compton camera is being developed. Sato et al [ 187 ] also performed radiation imaging while the platform is moving by measuring the self-position and posture of the camera in each detection (using time stamps), which allowed extraction of the direction of the Compton cones. Replacing the gamma imager by a 3D-LiDAR, it was also possible to do a second autonomous flight to obtain the 3D topographical measurement and to create a 3D radiation distribution map.…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
“…[ 9 , 126 ]. Use of gamma cameras coupled to small UAVs [ 187 ]—these platforms are extremely maneuverable and can be used for autonomous source localization; however, some improvements are necessary in the development of compact and lightweight gamma cameras, reduction of the acquisition times, and image compensation due to the movement of the source or detection platform, while acquiring the gamma image [ 230 ]. Detection system change—normally, radiation detection systems are expensive, and there is a reluctance in changing them by new ones (using emerging technologies).…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
“…The authors in [112] developed a remote radiation imaging system comprising a lightweight Compton camera and a 3D LiDAR mounted on a multi-copter drone to remotely measure the distribution of radioactive substances. The Compton camera mounted on the drone has the ability to visualize a 3D distribution of radioactive substances in difficult-to-return zones.…”
Section: Mobile Radiation Monitoring Using Uav 621 Radiation Monitoring Using Conventional Uavmentioning
confidence: 99%
“…However, in the events of theft and loss of sources or undesired acts of terrorism using such sources, it is necessary to identify multiple sources over a wide search area rapidly [1]. Several methods for radiation source identification have been developed [2][3][4][5][6][7]. For example, Huo et al reported a method to estimate the location and intensity of radiation sources by using a mobile robot equipped with a Geiger-Müller (GM) counter and laser range sensor [4].…”
Section: Introductionmentioning
confidence: 99%